An introduction to photosynthesis - Wilson, Agatha (New York, NY, USA Callisto Reference, 2015)
The most basic and significant aspect of life process on earth is linked to the process of photosynthesis. Photosynthesis is the most researched field amongst the scientific community. The present book examines the fundamentals of photosynthesis, and its impact on different life forms. The book contains important sections analyzing light and photosynthesis, the importance of carbon in photosynthesis, and discusses other significant topics related to the process of photosynthesis. The chapters are well-structured and are contributed by experts in the field. The readers will gain ample knowledge from the new findings documented in the book.
Includes bibliographical references.
Keywords: Photosynthesis -- Research